South Africa : Financial Sector Assessment Program-Technical Note on Financial Safety Net and Crisis Management. (IMF Staff Country Reports; Country Report, 2022)
This Technical Note sets out the findings and recommendations of the Financial Sector Assessment Program (FSAP) for South Africa on financial safety net and crisis-management arrangements. It primarily focuses on the arrangements for early intervention, recovery, resolution, and financial safety nets for banks in South Africa. To a lesser extent, the note also addresses issues relating to recovery and resolution applicable to insurers and Financial Market Infrastructure (FMI).